Familial Episodic Amaurosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
A family with a stereotyped unilateral or bilateral transient visual loss, that recurred many times daily and was associated with childhood epilepsy and familial hemiplegic migraine, is reported from University Hospitals, Geneva, Switzerland.